Estrategias de marketing para mejorar el posicionamiento de los productos de la Asociación Vinicola Salesiana, Lima 2018 - Terrones Deza, Victor Cesar (2018)
The present research work was carried out in the Salesian Wine Association, located in the city of Lima, whose objective was to carry out a study of marketing strategies that the Salesian Wine Company has been applying with the purpose of improving the positioning of the products it offers, Since the products offered are within a highly competitive framework, the research carried out is descriptive, not experimental, the Inductive-Deductive Method, Hypothetical-Deductive Method was used, the survey was used as a research technique, To validate the reliability of the data obtained, Cronbach's Alpha method was applied; the population was made up of the customers of the Salesian Wine Association, a representative sample was obtained through the statistical method to which the data collection instrument was applied, and with the information obtained it was possible to meet the objectives of the thesis, check the research hypothesis, and propose strategies to improve the positioning of the Association's products, obtaining as a main result that the study variables are positively related, and as a result of the correlational analysis of the variables, it was concluded that the Marketing strategies have a positive impact on the positioning of the products of the Salesian Wine Association.